Student Perceptions of the Use of Technology in Mathematics Learning - Ni Wayan Suardiati Putri; Kadek Suryati; Evi Dwi Krisna; Ni Kadek Ulan Cahyani (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2026)
The use of technology in mathematics learning is crucial for supporting digital learning in higher education, particularly in helping students understand abstract mathematical concepts. This study aims to determine students' perceptions of the use of technology in mathematics learning. The study used a quantitative descriptive approach with a survey method. The subjects were 130 students who had participated in technology-based mathematics learning. The instrument was a five-level Likert-scale questionnaire with six indicators: ease of use, benefits of technology, interest and motivation, interaction and engagement, obstacles to use, and support for understanding mathematical concepts. Data were analyzed using percentages. The results showed that students had positive perceptions. The dominant response was agreement for the ease of use indicator (53.54%), benefits of technology (51.69%), interest and motivation (44.15%), interaction and engagement (51.23%), and support for understanding concepts (46.00%). For the obstacles indicator, the highest response was neutral at 39.54%. Thus, technology is perceived as capable of supporting mathematics learning, although its optimization still requires the readiness of facilities, networks, and user skills.